THREE HIDDEN PROBLEMS FACED BY SECOND YEAR UNIVERSITY STUDENTS ON LISTENING SKILL - Hartatya Novika; Muhammad Arbain; Yudha Aprizani (Intensive Journal, 2020)
This research is aimed at identifying the second-year university students’ perspective on the problems encountered in listening comprehension particularly dealing with listening task, effect of the problem and context. The design employed in this research belongs to descriptive research. 50 second-year university students were selected voluntarily. The research result showed problematic uses in which EFL learners have difficulties understanding listening text while the native speakers with varied and non-familiar accents. Besides, they were not able to understand meanings which are not pronounced clearly.